1196Trajectories of disability throughout adolescence and labour force status as a young adult. (2nd September 2021) - Shields, Marissa; King, Tania; Dimov, Stefanie; Kavanagh, Anne; Spittal, Matthew
Abstract: Background: Young people with disabilities have poorer labour force outcomes than their peers without disabilities. Existing studies typically assess disability at one time point, obscuring potential variation in the experience of disability over time. This study aimed to identify trajectories of disability during childhood/adolescence and assess associations between trajectory membership and labour force status in young adulthood. Methods: Group-based trajectory modeling was applied to disability status information from Waves 2-7 (age 4/5 to 16/17 years) of the Longitudinal Study of Australian Children; labour force participation (employed, unemployed, not in the labour force (NILF)) was measured at Wave 8 (18/19 years). Two logistic regression models assessed the relationship between trajectory group membership and labour force participation, adjusted for confounders. Results: Four trajectory groups were identified: low (75.5% of cohort), low increasing (9.7%), high decreasing (10.9%), and consistently high (3.9%) prevalence of disability. Compared to individuals in the low trajectory (reference group), individuals in the consistently high trajectory had increased odds of being NILF at age 18/19 years (AOR 3.48, 95%CI 2.14, 5.68). Individuals in the low increasing trajectory had increased odds of unemployment at age 18/19 years compared to the reference group (AOR 2.93, 95%CI 1.91-4.48). Conclusions: Results suggest that early experiences of disability among young Australians may differentially impact future labour force outcomes. Key messages: Additional supports to prepare young people for the labour force should focus on individuals with consistently high or increasing prevalence of disability trajectories.